Poverty and Economic Growth in Egypt, 1995-2000 - El-Laithy, Heba; Lokshin, Michael; Banerji, Arup (World Bank, Washington, DC, 2014)
After a decade of slow economic growth Egypt's rate of growth recovered in the late 1990s, averaging more than five percent a year. But the effect of this growth on poverty patterns has not been systematically examined using consistent, comparable household datasets. In this paper, the authors use the rich set of unit-level data from the most recent Egyptian household surveys (1995-96 and 1999-2000) to assess changes in poverty and inequality between 1995 and 2000. Their analysis is based on household-specific poverty lines that account for the differences in regional prices, as well as differences in the consumption preferences and size and age composition of poor households. The results show that average household expenditures rose in the second half of the 1990s and the poverty rate fell from 20 percent to less than 17 percent. But, in addition to the ongoing divide in the urban-rural standard of living, a new geographical/regional divide emerged in the late 1990s. Poverty was found predominantly among less-educated individuals, particularly those working in agriculture and construction, and among seasonal and occasional workers. These groups could suffer the most from the slowing economic growth evident after 1999-2000.